Molecular identification and probiotic characterization of isolated yeasts from Iranian traditional dairies - Saber, Amir; Yari Khosroushahi, Ahmad; Faghfoori, Zeinab; Seyyedi, Maryam; Alipour, Beitollah (Progress in Nutrition, 2019)
Yeasts as natural live microorganisms with probiotic properties are important in human nutrition and improving health due to their ability to ferment food production. The traditional fermented dairy foods as a rich source of wild native strains of yeasts can introduce new strains with probiotic properties. The aim of this study is to isolate and identify yeasts from Iranian traditional dairy products and characterize their probiotic properties. Fifty-five fresh stored yogurt and cheese were purchased from rural areas and the native yeasts of them were characterized using the intragenic transcribed spacer-PCR (ITS1 and ITS2) regions through specific primers and the amplified genes were sequenced. Also, some probiotic assessment tests including; resistant to acid and bile, antimicrobial activity and antifungal susceptibility were performed. Seventeen yeast species belonged to 4 genera were identified as Pichia, Kluyveromyces, Saccharomyces, and Candida. The difference between survival rates after treatment with acid (pH 2.0) and bile salts (0.3%) for 3h were not significant for 24 strains. Finally, after antimicrobial activity and antifungal tests 5 yeast strains indicated potentially probiotic properties. Our findings showed that among the isolated yeasts from home-made cheese and yogurt, Pichia fermentans and Pichia kudriavzevii were the predominant strains. Meanwhile, 10 strains revealed antifungal susceptibility but only 5 strains were susceptible to all antifungals, so we can consider these strains as a native probiotic for implicating in food industries, however extra examinations required for introduction into food products.